A Rapid Review of Electronic Medical Record (EMR) Implementation in Midwifery Care Services - Kriska Afri Juliandari; Septiana Ade Ammalia; Dewi Anggraini Padmaningtyas; Rohani Rohani; Cesa Septiana Pratiwi (Jurnal Bidan Cerdas, 2025)
Background: one of the common problems associated with breastfeeding and exclusive breastfeeding is breast swelling until the incidence rate reaches 20%-70% in nursing mothers. Swelling of the breasts can be prevented non-pharmacologically, namely by compressing cold cabbage leaves and the marmet technique. Purpose: The study aimed to compare the effectiveness of cold cabbage leaf compresses and the Marmet technique in preventing postpartum breast swelling in normal puerperal mothers. Methods: Types of pre-experimental research with One-shot case study design namely cabbage compress (duration 30 minutes) and marmet technique given 1 time. The total sample of 30 respondents, was divided by 15 respondents in each group and sampling by non-probability sampling type of consecutive sampling. The measuring instrument uses an observation sheet containing a six-point engorgement scale (SPES). Data was analyzed using the Wilcoxon and Mann-Whitney test (p<0,05). Results: analysis of the effect of cold cabbage leaf compress management and marmet technique on the prevention of breast swelling for normal puerperal mothers was obtained in cold cabbage leaf compresses p-value of 0.014 and in the marmet technique obtained p-value 0.317. The results of the analysis of the effectiveness of the two techniques were obtained with a p-value of 0.007 or <0.05. Conclusion: Cold cabbage leaf compresses were significantly more effective in reducing breast swelling compared to the Marmet technique in the Independent Practice of Midwives (PBM) Setia of Palu City. It is recommended to use both techniques in helping to prevent breast swelling for normal puerperal mothers.